2018
DOI: 10.1111/acps.12879
|View full text |Cite
|
Sign up to set email alerts
|

No differences in olanzapine‐ and risperidone‐related weight gain between women and men: a meta‐analysis of short‐ and middle‐term treatment

Abstract: The present meta-analysis revealed that sex differences in AP-related weight gain have been under investigated hampering the detection of sex-specific patterns. In chronic patients switching to olanzapine or risperidone receiving short-or middle-term treatment, AP were associated with weight gain in both sex subgroups and no significant differences were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 87 publications
(120 reference statements)
0
8
0
Order By: Relevance
“…In fact, weight gain may be more rapid in short‐ versus long‐term treatment with olanzapine 22 . Data concerning risk differentiation for olanzapine‐induced weight gain between women and men may present inconsistencies 9,19 . There is also contrasting evidence regarding the role of olanzapine dose on its effects on weight gain; for example, higher olanzapine daily doses resulted in larger weight gain on the long term in a retrospective cohort 22 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, weight gain may be more rapid in short‐ versus long‐term treatment with olanzapine 22 . Data concerning risk differentiation for olanzapine‐induced weight gain between women and men may present inconsistencies 9,19 . There is also contrasting evidence regarding the role of olanzapine dose on its effects on weight gain; for example, higher olanzapine daily doses resulted in larger weight gain on the long term in a retrospective cohort 22 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 8 Specifically, patients treated with almost all antipsychotic agents demonstrated essential weight gain as well as elevated risk of metabolic syndrome compared to antipsychotic‐naïve patients with SMIs. 1 , 8 Unfortunately, available evidence on predictors or moderators of the risk of metabolic abnormalities within the context of antipsychotic treatment may present some inconsistencies, 1 , 9 although low baseline body mass index (BMI) and younger age have been invariably associated with greater antipsychotic‐induced weight gain. 10 Further, the risk of metabolic alterations seems to vary between different antipsychotic medications 11 ; for instance, patients treated with olanzapine and clozapine are at higher risk of weight gain and metabolic syndrome compared to other first‐ or second‐generation antipsychotics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include studies demonstrating an increased risk of AP-induced weight gain and obesity in women (Kraal et al, 2017; Lau et al, 2016; Li et al, 2016; Seeman, 2010). However, these findings have been challenged by a meta-analysis that did not find such differences (Schoretsanitis et al, 2018). Some APs induce prolactin secretion in patients, and a higher baseline prolactin level in women may cause them to be more sensitive to hyperprolactinemia symptoms (Seeman, 2009), whereas an association between high prolactin levels and impaired cognitive processes in early psychosis may be restricted to men (Montalvo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Little data exist on sex differences in SGA-related weight gain. A recent meta-analysis of adult samples reported no difference in weight gain between male and female patients treated with SGAs (Schoretsanitis et al, 2018), and a similar result was reported in adolescent patients treated with risperidone (Kelly et al, 1998), and in children and adolescents with early-onset schizophrenia spectrum disorders (Taylor et al, 2018). In contrast, a single study reported that male sex is a risk factor for weight gain in adolescents treated with risperidone and olanzapine (Ratzoni et al, 2002).…”
Section: Discussionmentioning
confidence: 80%